Teachers' perception of men in the feminised occupations - Anna Dudak (Uniwersytet Kazimierza Wielkiego, 2019)
Occupational roles in the context of gender stereotypes are subject to a growing number of research explorations. This is mainly due to ongoing changes in female and male social functioning, including occupational roles. The discussion presented in this article concerns the functioning of males in female-dominated occupations. The aim of the research was to diagnose the opinion of active teachers on the functioning of males in female-dominated occupations in the context of gender stereotypes. Attention was also drawn to the opinions of the respondents concerning the consequences of stereotypical evaluation of males' work in professions dominated by females.